Dynamics of Border Conflict Resolution Between Indonesia-Timor Leste - Armita Arvanti; Bayu Setiawan; Syamsunasir Syamsunasir; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Border areas are areas that are geographically directly adjacent to other countries. The border area is also one of the strategic areas, where the area that nationally concerns the lives of many people, both in terms of political, economic, social, cultural, and hankam interests. Border conflicts are usually particularly vulnerable if the contested territory has excellent natural and economic resource potential. The purpose of this study is to describe the factors that cause conflict and the urgency of boundary affirmation and describe efforts to resolve boundaries through regulation and non-regulation. The method used is a qualitative method with a type of descriptive approach through literature study. Based on the results of the study, it is understood that the settlement of Indonesia's border with Timor-Leste will be carried out peacefully, without the threat of violence, and with full respect for international law. This article seeks to understand the Indonesia-Timor Leste border dispute from the perspective of international relations. Three strategies can be taken by Indonesia to resolve this dispute, namely military confrontation, the use of formal institutions such as international organizations, and the use of informal institutions namely norms, beliefs, ideas, and values. This article argues that to resolve the dispute between Noel Besi/Citrana and Bijael Sunan/Oben it is not enough to rely on international treaties alone, Indonesia needs to put more emphasis on the importance of understanding the norms, beliefs, ideas, and values of indigenous peoples living in the disputed area. The role of the government in efforts to maintain the integrity of the country's territory through bilateral communication and cooperation can then be utilized by local actors to resolve conflicts and participate in defending the territory.